Inducible gene modification in the gastric epithelium of Tff1‐CreERT2, Tff2‐rtTA, Tff3‐luc mice. Issue 12 (25th October 2016) - Thiem, Stefan; Eissmann, Moritz F.; Stuart, Emma; Elzer, Joachim; Jonas, Anna; Buchert, Michael; Ernst, Matthias
Abstract: Temporal and spatial regulation of genes mediated by tissue‐specific promoters and conditional gene expression systems provide a powerful tool to study gene function in health, disease, and during development. Although transgenic mice expressing the Cre recombinase in the gastric epithelium have been reported, there is a lack of models that allow inducible and reversible gene modification in the stomach. Here, we exploited the gastrointestinal epithelium‐specific expression pattern of the three trefoil factor ( Tff ) genes and bacterial artificial chromosome transgenesis to generate a novel mouse strain that expresses the CreERT2 recombinase and the reverse tetracycline transactivator (rtTA). The Tg( Tff1‐CreERT2 ; Tff2‐rtTA;Tff3‐Luc ) strain confers tamoxifen‐inducible irreversible somatic recombination and allows simultaneous doxycycline‐dependent reversible gene activation in the gastric epithelium of developing and adult mice. This strain also confers luciferase activity to the intestinal epithelium to enable in vivo bioluminescence imaging. Using fluorescent reporters as conditional alleles, we show Tff1‐CreERT2 and Tff2‐rtTA transgene activity in a partially overlapping subset of long‐term regenerating gastric stem/progenitor cells. Therefore, the Tg( Tff1‐CreERT2 ; Tff2‐rtTA;Tff3‐Luc ) strain can confer intermittent transgene expression to gastric epithelial cells that have undergone previous gene modification, and may be suitable to genetically model therapeutic intervention during development, tumorigenesis, and other genetically tractable diseases. Birth Defects Research (Part A) 106:626–635, 2016. © 2016 Wiley Periodicals, Inc.